Effects of 6-week sprint interval training compared to traditional training on the running performance of distance runners: a randomized controlled trail - Jin, K.; Cai, M.; Zhang, Y.; Wu, B.; Yang, Y. (Frontiers in Physiology, 2025)
Introduction: This study aimed to compare the effects of sprint interval training versus traditional training on running performance in well-trained male distance runners.